2017
DOI: 10.1136/bcr-2017-219393
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib as a novel treatment option in hereditary haemorrhagic telangiectasia

Abstract: A 70-year-old patient with known hereditary haemorrhagictelangiectasia (HHT) was seen regularly in our outpatient clinic. He underwent multiple therapeutical interventions, including both surgical and medical, for the treatment of recurrent epistaxis without sustained success. Due to a concurrent diagnosis of idiopathic pulmonary fibrosis, treatment with the tyrosine kinase inhibitor nintedanib was initiated, after which point the patient reported a dramatic and unanticipated improvement in his epistaxis and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
(11 reference statements)
0
8
0
2
Order By: Relevance
“…The tyrosine kinase inhibitor Nintedanib, which targets the platelet-derived growth factor, fibroblast growth factor and vascular endothelial growth factor receptors, has been used in one HHT2 patient following the diagnosis of Interstitial Pulmonary Fibrosis [47] with encouraging results. His Epistaxis Severity Score significantly decreased.In France, we are implementing a multicenter, randomized, drug versus placebo study to evaluate efficacy of Nintedanib treatment per os on epistaxis duration in HHT patients with moderate to severe epistaxis (NCT03954782).…”
Section: Main Textmentioning
confidence: 99%
“…The tyrosine kinase inhibitor Nintedanib, which targets the platelet-derived growth factor, fibroblast growth factor and vascular endothelial growth factor receptors, has been used in one HHT2 patient following the diagnosis of Interstitial Pulmonary Fibrosis [47] with encouraging results. His Epistaxis Severity Score significantly decreased.In France, we are implementing a multicenter, randomized, drug versus placebo study to evaluate efficacy of Nintedanib treatment per os on epistaxis duration in HHT patients with moderate to severe epistaxis (NCT03954782).…”
Section: Main Textmentioning
confidence: 99%
“…Several receptor tyrosine kinase (RTK) inhibitors that target VEGFR2 are FDA/EMA approved; one of these, pazopanib, showed beneficial effects in ALK1-deficient mice (39) and in a cohort of patients with HHT (40). A recent case study reported that nintedanib (Nin, BIBF 1120), a VEGFR2-targeting RTK inhibitor that is approved for idiopathic pulmonary fibrosis (IPF) treatment, produced marked reductions in epistaxis and skin telangiectasias in a patient affected by both HHT and IPF (41). Nin is of particular interest compared with other classical RTK inhibitors because it has a narrow spectrum of inhibition and is associated with minimal adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…BZ is used (off-label) for antiangiogenic strategy in HHT patients with severe bleeding or symptomatic liver AVMs, in order to reduce bleedings and excessive number of abnormal mucosa vessels. TKIs (pazopanib, nintenadib, sunitinib or buparlisib) and thalidomide have also been used or are planned to be used in clinical trials [ 22 , 83 , 101 , 102 ] ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, patients will be monitored for 24 weeks: 12-weeks of oral treatment plus 12-weeks of follow-up. Theoretically, nintedanib, as a non-specific/wide range TKI, should allow a reduction of epistaxis in HHT [ 83 ].…”
Section: Therapeutic Pathways/strategies Of Pharmacological Treatmmentioning
confidence: 99%